EVALUASI PENERAPAN PENANGGULANGAN KEBAKARAN DI PT PELINDO IV BALIKPAPAN - Impol Siboro; Munahar Munahar; Astrid Clara Christianty (Program Studi D-IV K3, 2021)
An emergency is an event or series of events that threaten and disrupt people's lives and livelihoods caused, either by natural factors and/or non-natural factors as well as human factors, resulting in human casualties, environmental damage, property losses, and psychological impacts. Fire control is all efforts to prevent fires by various efforts to control each manifestation of energy, procurement of fire protection facilities and rescue facilities and the establishment of emergency response organizations to eradicate fires. In this study, the author discusses the application of fire prevention at PT Pelindo IV Balikpapan. This study uses a descriptive research method with a qualitative approach where the author uses a checklist sheet regarding the suitability of fire prevention and interview guidelines to conduct interviews with sources who are considered to be the most knowledgeable about fire prevention at PT Pelindo IV Balikpapan. The results of the study found that the suitability of the emergency response system was 61.11% and life-saving facilities was 85.71% with an average value of suitability for fire prevention at PT Pelindo IV Balikpapan of 73.41% with the